2018
DOI: 10.1186/s40643-018-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the secretion pathway maximizes the effects of mixed feeding strategy for glucose oxidase production in the methylotrophic yeast Pichia pastoris

Abstract: Background: A mixed feeding strategy (co-feeding of complex carbon sources with methanol) has become a common practice for process development in Pichia pastoris to increase cell biomass and enzyme production levels. However, in some cases mixed feeding did not have a significant impact or even had a negative effect on specific enzyme productivity. We hypothesized that this may be due to a bottleneck in the protein secretion pathway caused by too strong protein expression as a result of mixed feeding operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Combining strain and process engineering in P. pastoris has yielded promising results, as showcased by two recent examples from Che and colleagues and Bankefa and colleagues [76,77]. In the former, a combination of codon optimization, gene dosage, and fermentation optimization resulted in the production of 12 690 U/ml of fibase, while the latter showed how a mixed-feeding strategy combined with secretory pathway engineering led to a threefold increase in glucose oxidase production to 787.4 U/ml.…”
Section: Signal Sequences and Process Controlmentioning
confidence: 96%
“…Combining strain and process engineering in P. pastoris has yielded promising results, as showcased by two recent examples from Che and colleagues and Bankefa and colleagues [76,77]. In the former, a combination of codon optimization, gene dosage, and fermentation optimization resulted in the production of 12 690 U/ml of fibase, while the latter showed how a mixed-feeding strategy combined with secretory pathway engineering led to a threefold increase in glucose oxidase production to 787.4 U/ml.…”
Section: Signal Sequences and Process Controlmentioning
confidence: 96%
“…Although some proteins such as human serum albumin and antibody fragments can be highly secreted from native host [18]; however, majority of others are still being reported in low level secretion, owing to different bottlenecks such as; mis-folding, sub-optimal conditions and secretion limitation pathways which may result in accumulation of these proteins in the endoplasmic reticulum, among others [19]. Nevertheless, efforts had been directed towards overcoming this bottleneck [20,21], but unfortunately, the sources of these proteins are rarely investigated.…”
Section: Table 2 Morphological Features Of the Fungal Isolatesmentioning
confidence: 99%
“…19,66,[73][74][75][76][77][78][79][80] In addition, strategies of formulating the fermentation medium 73,81 and computational tools 82 have proven to be powerful tools to increase glucose oxidase productivity. As an example, Bankefa et al 73 reported a strategy of co-feeding complex carbon sources (e.g., yeast extract) with methanol, combining a secretory pathway engineering in a Pichia pastoris strain containing the gene encoding glucose oxidase from A. niger. Using this strategy, the volumetric extracellular activity of glucose oxidase in a 1 L fermenter was enhanced by around 3-fold compared to that reached when utilizing a recombinant P. pastoris strain containing only the gene encoding glucose oxidase.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…Both glucose oxidases are 10-16 wt% glycosylated with high-mannose type carbohydrates. 14,16,18,75,[84][85][86][87] Bankefa et al 73 reported that the SDS-PAGE analyses of glucose oxidase from A. niger extracellularly expressed by a recombinant P. pastoris strain showed a protein band of approximately 80 kDa, while its theoretical size was 63.5 kDa. This higher molecular mass of the enzyme subunit was attributed to enzyme glycosylation (around 21 wt%).…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%